Changes in Women’s Menstruation Cycle After COVID-19 Vaccination and Infection - Ulfa, Maria; Tinartayu, Seshy; Fitriani, Dwi Kartika Nur; Merkusi, Sweetina; Veterini, Varianidia (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2023)
Since the COVID-19 case was discovered, Indonesia has been one of the affected nations and found various COVID-19 infection and immunization risks. Most females are in the menstrual cycle following COVID-19 infection, regardless of the number of days between cycles, blood quantity, or menses duration. This study examines the changes in menstruation post-COVID-19 infection and vaccination. This study used a cross-sectional observational study with an online questionnaire. The 758 female respondents in Yogyakarta were divided into two groups: 532 females who received vaccination and never have been infected with COVID-19 (Group A) and 226 females with a history of being infected with COVID-19 and vaccination (Group B). The data was analyzed using SPSS 26. The results found that most respondents aged 17-25 (90.24%) were students (80.87%). Both two groups had acne on Pre-menstrual syndrome (28.16%), 5-8 days of menstrual duration (73.75%), 30 days of menstruation duration length (57%), and the regular menstruation volume (63.19%) after COVID-19 vaccination. The comparative analysis of menstruation changes in two groups (p0.05), including menstrual duration (0.771), menstrual duration length (0.609), and menstrual volume (0.476) after COVID-19 vaccination. In conclusion, there was no significant difference in menstrual change between Group A and Group B. After vaccination, healthcare professionals can promote post-COVID-19 immunization counseling and services to women who experience an abnormal menstrual cycle.